2021
DOI: 10.1590/1678-4499.20200404
|View full text |Cite
|
Sign up to set email alerts
|

Could the umbel order selection and GA3 treatment improve seed germination in Amazon chicory species?Could the umbel order selection and GA3 treatment improve seed germination in Amazon chicory species?

Abstract: This study aimed to estimate the production of seeds per umbel and to assess both the effect of gibberellic acid (GA3) and umbel order on seed germination in Amazon chicory species. The experiment was conducted in two steps. Firstly, traits related to seed production were evaluated. Afterward, a germination test was carried out, and the following parameters were assessed: germination speed index (GSI), average germination time (AGT), germination percentage (%G), percentage of abnormal seedlings (%AS), and perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…These events ultimately lead to seed growth, beginning with water uptake and ending with radicle elongation (Ma et al, 2022). GAs are positive regulators of seed germination (Moraes et al, 2021). We found that three factors were important for improving and accelerating the germination of C. gigantea seeds, namely, the photoperiod (hours of light), incubation temperature, and exogenous application of GA 3 .…”
Section: Discussionmentioning
confidence: 83%
“…These events ultimately lead to seed growth, beginning with water uptake and ending with radicle elongation (Ma et al, 2022). GAs are positive regulators of seed germination (Moraes et al, 2021). We found that three factors were important for improving and accelerating the germination of C. gigantea seeds, namely, the photoperiod (hours of light), incubation temperature, and exogenous application of GA 3 .…”
Section: Discussionmentioning
confidence: 83%